A study on awareness of health effects of tobacco consumption among medical students and impact of modular training - Madappady, Sajjan; Kumar, Hemant; Jayaram, S.; Brahmbhatt, Krutarth; Anil, Manjula; Chakraborty, Tamal; ., Shwethashree; H. R., Sindhushree (International Journal Of Community Medicine And Public Health, 2018)
Background: Tobacco kills more than seven million people each year. In India tobacco kills nearly one million people each year and many of these deaths occur among people who are very young. Studies indicate that approximately 70% of all tobacco users would like to quit smoking and tobacco use. Methods: A non-randomized, cross sectional study was conducted in a Medical College in Mangaluru (Karnataka) which included medical students from first year to third year. A module developed by “Quit Tobacco International” was used for the purpose of training and counselling the selected medical students, focusing on the specific effects of tobacco, depicting simulated case scenarios. Results: A total of 404 medical students were included in the study. It was observed that 15.9% males and 5.3% females among first year students, 21.0% males and 5.3% females among second year students and 24.6% males and 9.2% females among third year students had smoked at some point in their life while the among current users, the prevalence of smoking was found to be much higher i.e. 8.7% and 2.6% among first year students, 9.9% and 3.5% among second year students; while it as highest among third year students i.e. 14% and 4.6%; among boys and girls respectively. Conclusions: The study brings out the need for inclusion of structured teaching and training of our medical students on harmful effects of tobacco use and its cessation techniques.